2012
DOI: 10.1002/hbm.22008
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of the self‐memory system: New insights from a meta‐analysis

Abstract: The self has been the topic of philosophical inquiry for centuries. Neuropsychological data suggest that the declarative self can be fractionated into three functionally independent systems processing personal information at several levels of abstraction, including episodic memories of one's own life (episodic autobiographical memory, EAM), semantic knowledge of facts about one's own life (semantic autobiographical memory, SAM), and semantic summary representations of one's personal identity (conceptual self, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
243
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(260 citation statements)
references
References 110 publications
(142 reference statements)
16
243
1
Order By: Relevance
“…The results of this paper build on current conceptual models that view personal memory as a form of memory that incorporates both episodic and semantic information (Conway, 2005;Haslam et al, 2011;Martinelli et al, 2013;Renoult et al, in press). However, much remains unknown about the neural and cognitive bases of personal memory.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The results of this paper build on current conceptual models that view personal memory as a form of memory that incorporates both episodic and semantic information (Conway, 2005;Haslam et al, 2011;Martinelli et al, 2013;Renoult et al, in press). However, much remains unknown about the neural and cognitive bases of personal memory.…”
Section: Discussionmentioning
confidence: 57%
“…However, much remains unknown about the neural and cognitive bases of personal memory. In their meta-analysis of functional neuroimaging research on personal memory, Martinelli et al (2013) revealed that autobiographical fact retrieval in healthy adults was associated with a widely distributed neural network that includes anterior and posterior cortical midline structures, frontal and temporal gyri, thalamus, fusiform gyrus, and the MTL. We have demonstrated that one region in this network, namely the MTL, is needed for retrieval of only a subset of autobiographical facts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, memories of specific personal experiences (i.e., events that happened at a particular place and time in an individual's life) are compared with the retrieval of non-personal information (e.g., non-personal semantic knowledge or stimuli that have been learned in the laboratory before the scanning session). Neuroimaging evidence indicates that such autobiographical memory retrieval is associated with activations in the mPFC, medial and lateral temporal areas, posterior cingulate/retrosplenial cortex, and inferior parietal lobes (for meta-analyses, see Kim, 2012;Martinelli, Sperduti, & Piolino, 2013;McDermott, Szpunar, & Christ, 2009;Spreng, Mar, & Kim, 2009;Svoboda, McKinnon, & Levine, 2006). Furthermore, lesion data have revealed that damage to these areas is associated with deficits in autobiographical memory retrieval (Philippi, Tranel, Duff, & Rudrauf, 2015).…”
Section: Neural Correlates Of Directed and Spontaneous Self-referentimentioning
confidence: 99%
“…A recent meta-analysis of neuroimaging studies (Martinelli et al, 2013) Subsequent studies have detected similar activations in the mPFC, posterior cingulate, and lateral temporal cortex when reflecting on personal goals, especially promotion goals (i.e., things the individual would like to achieve) (for a meta-analysis, see Stawarczyk & D'Argembeau, 2015).…”
Section: Neural Correlates Of Directed and Spontaneous Self-referentimentioning
confidence: 99%